Varnost v lokalnih skupnostih – izsledki raziskovanja zaznav varnosti v Sloveniji: konferenčni zbornik / 3. nacionalna konferenca o varnosti v lokalnih skupnostih, 28. november 2017, Novo mesto, Slovenija (University of Maribor Press, 2017)
Safety and Security in Local Communites – results of research on safety perceptions in Slovenia : 3rd National Conference on Local Safety and Security, November 28th, 2017, Novo mesto, Slovenia. The conference proceedings present peer reviewed papers presented at the third national conference on local safety and security in Slovenia in November 2017. A lead topic of the conference summarizes results of research on safety perceptions, which was done in 24 local communities in the spring in 2017. The main aim of the papers is proposing solutions for more efficient assurance of safety/security in local communities (smaller, middle and larger municipalities) in Slovenia. The papers in the proceedings discuss various aspects of safety and security in local communities, such as perception of safety/security and risks in local communities (perception of crime, sources of threats, safety in urban areas, police presence, and social cohesion); expectations and effectiveness of ensuring safety and security (perception and effectiveness of community policing, perception of the tasks of armed forces, migration, and perception of threats in cyber space); and practices of ensuring safety and security in local communities (legal regulation of municipalities, good practices of solving safety issues in the area of Police directorate Novo mesto and Murska Sobota, and perception of ensuring local safety and security through the perspective of different stakeholders).